Is There a Role for SARS-CoV-2/COVID-19 on the Female Reproductive System? - D’Ippolito, Silvia; Turchiano, Francesca; Vitagliano, Amerigo; Scutiero, Gennaro; Lanzone, Antonio; Scambia, Giovanni; Greco, Pantaleo (Frontiers in Physiology, 2022)
Coronavirus disease (COVID-19) has emerged as a very serious pandemic caused by the rapidly evolving transmission of the coronavirus SARS-CoV-2. Since its outbreak in 2020, the SARS CoV-2 has represented an important challenge for the physicians due to its well known respiratory sequelae. To date, the role of SARS-CoV-2 infection on organs and systems other than lungs and respiratory tract remains less clear. In particular, it remains to be investigated whether the reproductive system can be affected by the SARS-CoV-2 in the long term-period or, in alternative, drugs used to treat COVID-19 might impact the reproductive systems and, in turn, fertility. What is known is that SARS-Cov-2 binds to target cells of host through different receptors including angiotensin-converting enzyme 2 (ACE2), neuropilin-1, AXL and antibody-FcɣR complexes. ACE2 physiologically regulates both the expression of angiotensin II (Ang II) as well as Ang-(1-7) to exerts its physiological functions. The reproductive system abundantly expresses ACE2 and produces Ang-(1-7), starting from precursors which are locally generated or derived from systemic circulation. Ang-(1-7) plays an important role of stimulus to the growth and maturation of ovarian follicle as well as to ovulation. Also human endometrium expresses Ang-(1-7), mainly during the post-ovulatory phase. Animal and human observational studies demonstrated that Ang-(1-7) is involved in the maternal immune response to pregnancy and its deficiency is associated with a defective placenta development. a vasorelaxant effect, in the physiological mechanism of corpus cavernosum activation. In our manuscript, we review the current knowledge about whether SARS-CoV-2 may impact the female reproductive system. We further explain the possible molecular mechanism by which SARS-CoV-2 might affect ovarian, endometrial and female genital tract cells.